Analisis Faktor Yang Mempengaruhi Permintaan Agregat Di SUmatera Barat (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2017)
The purpose of this research are to know and analysis influence inflation, the money supply, interest rates , government spending , consumption and exchange rate on aggregate demand in West Sumatra . The form of time series data from the first quarter of 2000 - the fourth quarter of 2010. This study uses a double linear regression model analysis tool with the Ordinary Least Square method ( OLS ). The results showed that inflation , money supply , interest rates , government spending and consumption have a significant effect on aggregate demand in West Sumatra.